The Real Effects of Credit Ratings: The Sovereign Ceiling Channel - ALMEIDA, HEITOR; CUNHA, IGOR; FERREIRA, MIGUEL A.; RESTREPO, FELIPE (Journal of Finance, 2017)
ABSTRACT We show that sovereign debt impairments can have a significant effect on financial markets and real economies through a credit ratings channel. Specifically, we find that firms reduce their investment and reliance on credit markets due to a rising cost of debt capital following a sovereign rating downgrade. We identify these effects by exploiting exogenous variation in corporate ratings due to rating agencies' sovereign ceiling policies, which require that firms' ratings remain at or below the sovereign rating of their country of domicile.